Benefits of Funding Tertiary Education in Nigeria - Ogunode , Niyi Jacob; Olowonefa, Jethro Abiodun; Suleiman, Sanusi (Researchparks Publishing, 2023)
This paper discussed the benefits of funding tertiary education adequately in Nigeria. Secondary data collected from print and online publications were used for the paper. The paper concluded that adequate funding of tertiary institutions in Nigeria will lead to sufficient funds in the various higher institutions, development of infrastructural facilities, employment of adequate staff, increment in salaries and welfares packages of staffs, reduction in brain-drain problems, prevention of strike actions in the institutions, attraction of international lecturers, research development, improvement in international ranking and attainment of an effective staff training programme. The paper suggested increasing investment in tertiary education. Tertiary institutions should be allowed to charge tuition fees within the parameters set by the government, but the Education Bank needs to be established to offer federal government-backed loans to students who may require them. Federal, state and institutional scholarship awards to help indigent students to pay tuition. Government institutionalized endowment funds for universities to expand their pool of funds. Tertiary institution should use their alumni to generate more revenue and give them incentives to contribute to their university endowment programmes. The government should institutionalize a new model of funding for tertiary education that needs to be developed in a way that will set objective parameters for the allocation of funds from the tertiary education trust fund (TETFUND) based on verified outputs in teaching, research and community service